Naming trends of Lithuanian emigrants in Ireland, Norway, and Germany (1991–2020), with focus on names of Baltic origin: Tendencias en los nombres de hijos de emigrantes lituanos en Irlanda, Noruega y Alemania (1991–2020), con foco en nombres de origen báltico - Sinkevičiūtė , Daiva (Onomástica desde América Latina, 2025)
This article examines naming trends among Lithuanian emigrants who give their children Baltic names in Ireland, Norway, and Germany, in comparison to those in the United Kingdom (see Sinkevičiūtė 2024a). The aim is to highlight that the Baltic names given to children in the major countries of emigration from Lithuania between 1991 and 2020 reflect the ethnic identity attributed to them by their parents, and that the tendency among emigrants to choose Baltic names is a regular and stable phenomenon. The qualitative and quantitative analysis of names focuses on the origin and structure of Baltic names to identify their systemic characteristics. This analysis revealed that, across all countries, the most common names are derived from natural phenomena and objects, Lithuanian pagan goddesses and gods, as well as notable historical and legendary figures from Lithuania’s past. Euphony also appears to play a role in naming. Furthermore, the same suffixes recur in names of different origins, and the same shortenings emerge from names sharing common initial elements. These findings complement previous studies on names given to children by emigrants during the same period. In particular, they demonstrate that the behavior of parents across the major countries of emigration from Lithuania is broadly similar when choosing Baltic names for their children (see Sinkevičiūtė 2024a). On the other hand, the study highlighted that Baltic names are more frequently given to girls. This indicates that, from the perspective of origin, girls’ names are more Lithuanian than boys’ names, as observed in the study of names with diacritic marks, which are more characteristic of girls (see Sinkevičiūtė 2024b).